Зооморфні метафори в "Словарі української мови" за редакцією Бориса Грінченка - Гуцуляк, Т.Є. (Лексикографічний бюлетень, 2014)
«Ukrainian language dictionary» edited by Boris Grynchenko is valuable source for researching of formation and development of lexico-semantic language system through which cultural and domestic people life’s feachures arise. Specificity of fixation in lexicography’s articles of extended meaning of words and figure of speech is analysed. In dictionary materials author deals with the representation of zoomorphic metaphor as one of the universal model of actual perception and language’s detection. Its function in people’s trade lexis and expression for emotive, expressive description of person is determined.